Heterogeneous activation of persulfate for the degradation of bisphenol A with Ni2SnO4–RGO. (7th April 2020) - Jiang, Ling; Xu, Xiangyang; Yuan, Jingjing; Zuo, Yuanjie; Tao, Yingrui; Yao, Dachuan; He, Guangyu; Chen, Haiqun
Abstract : The possible reaction mechanism of the activation of persulfate by Ni2 SnO4 –RGO for the degradation of BPA. Abstract : Spherical Ni2 SnO4 nanoparticles were uniformly loaded on reduced graphene oxide (RGO) sheets via a hydrothermal process. The obtained nickel stannate–reduced graphene oxide (Ni2 SnO4 –RGO) composite was used as a catalyst for activating persulfate (PS). The heterostructure composed of Ni2 SnO4 and RGO prevents both the agglomeration of Ni2 SnO4 nanoparticles and the restacking of RGO sheets. The synergy between the two components affords enhanced Ni2 SnO4 –RGO catalytic activity. Using Ni2 SnO4 –RGO to activate PS can degrade bisphenol A (BPA) at a faster rate with less PS, in comparison with the most recently reported catalysts. BPA solution (50 mL, 0.10 mM) can be 100% degraded by PS (0.02 g) within 30 min at pH 8 using Ni2 SnO4 –RGO (0.02 g) as the catalyst. Moreover, the preparation of Ni2 SnO4 –RGO is simple, inexpensive and environment-friendly. The radical scavenging study indicates that sulfate radicals ( ) and hydroxyl radicals (˙OH) are involved in the oxidation, in which plays a leading role. In addition, Ni2 SnO4 –RGO retains high catalytic activity after four consecutive cycles, exhibiting greatly enhanced stability in comparison with Ni2 SnO4 . Besides, the effect of different inorganic anions on the degradation was also explored.